Automatic Quantification of Interstitial Lung Disease From Chest Computed Tomography in Systemic Sclerosis - Carvalho, Alysson Roncally S.; Guimarães, Alan R.; Sztajnbok, Flávio R.; Rodrigues, Rosana Souza; Silva, Bruno Rangel Antunes; Lopes, Agnaldo José; Zin, Walter Araujo; Almeida, Isabel; França, Manuela Maria (Frontiers in Medicine, 2020)
Background: Interstitial lung disease (ILD) is a common complication in patients with systemic sclerosis (SSc) and its diagnosis contributes to early treatment decisions. Purposes: To quantify ILD associated to SSc (SSc-ILD) from chest CT images using an automatic quantification method based on the computation of the weight of lung interstitial opacities. Methods: Ninety-four patients with systemic sclerosis (SSc) underwent CT, forced vital capacity (FVC), and carbon monoxide diffusion capacity (DLCO) tests. Seventy-three healthy individuals without radiological evidence of lung disease served as controls. After lung and airway segmentation, the ratio between the weight of interstitial opacities (densities between -500 and +50 Hounsfield units) and the total lung weight (densities between -1000 and +50 HU) was used as an ILD indicator (ILD(%)=100 x [ LW( - 500 to + 50 HU)/LW(- 1000 to + 50HU)]). The cutoff of normality between controls and SSc was determined with a receiver operator characteristic (ROC) curve. The severity of pulmonary involvement in SSc patients was also assessed by calculating Z scores of ILD relative to the average interstitial opacities in controls. Accordingly, SSc-ILD was classified as SSc Limited-ILD (Z score < 3) and SSc Extensive-ILD (Z score ≥ 3 or FVC < 70%). Results: Seventy-eight (83%) SSc patients were classified as presenting SSc-ILD (optimal ILD threshold of 23.4%, 0.83 sensitivity, 0.92 specificity, and 0.94 AUC, 95% CI from 0.89 to 0.96, 0.93 positive predictive value, and 0.81 negative predictive value, p<0.001) and exhibited radiological attenuations compatible with interstitial pneumonia dispersed in the lung parenchyma. Thirty-six (38%) patients were classified as SSc Extensive-ILD (ILD threshold ≥ 29.6% equivalent to a Z score ≥ 3) and 42 (45%) as SSc Limited-ILD. Eighteen (50%) patients with SSc Extensive-ILD presented FVC<70%, being only 5 patients classified exclusively based on FVC. SSc Extensive-ILD also presented lower DLCO (57.9 ± 17.9% vs 73.7±19.8%; p<0.001) and total lung volume (2916±674 vs 4286±1136, p<0.001) compared to SSc Limited-ILD. Conclusion: The proposed method seems to provide an alternative to identify and quantify the extension of ILD in patients with SSc, mitigating the subjectivity of semi-quantitative analyzes based on visual scores.